1990
DOI: 10.1002/macp.1990.021911230
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of polystyrene particles with poly[(acylimino)ethylene] chains on the surface

Abstract: Polymer particles with poly[(acylimino)ethylene] chains on the surface were prepared by soapfree emulsion copolymerization of styrene with a styryl-type poly[(acylimino)ethylene] macromonomer. The macromonomer used was highly hydrophilic and soluble in water. The contour of the particles was d n e d by scanning electron microscopy. The copolymer particles were spherical and monodisperse. The average diameter of the particles was in the sub-micron range and smaller than that of pure polystyrene particles prepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The soap‐free emulsion copolymerization of styrene with the hydrophilic PROZO macromonomer 31 (R = Me or Et) produces monodisperse polymer particles in the submicrometer range 68. The diameter of the particles obtained with the macromonomer is smaller than that obtained without 31 .…”
Section: Applications Of Prozomentioning
confidence: 99%
“…The soap‐free emulsion copolymerization of styrene with the hydrophilic PROZO macromonomer 31 (R = Me or Et) produces monodisperse polymer particles in the submicrometer range 68. The diameter of the particles obtained with the macromonomer is smaller than that obtained without 31 .…”
Section: Applications Of Prozomentioning
confidence: 99%
“…It has been found that the copolymerization of a cyclic phosphonite 1 with a dialdehyde 2 undergoes the ringopening-closing alternating copolymerization (ROCAC) without added initiator to give an alternating copolymer 3. ROCAC belongs to a new concept in the polymerization chemistry.…”
Section: Discussionmentioning
confidence: 99%
“…In previous papers of this series we have developed a novel, general approach to the synthesis of new alternating copolymers, having the structure of a ring-opened unit from a cyclic monomer (A) and a ring-closed unit from a noncyclic, bifunctional monomer (B) (ring-opening-closing alternating copolymerization, ROCAC). [1][2][3][4][5][6] In this content, the extension of the scope of B-type monomers other than muconic acid1•5 and dialdehydes2•6 implies great synthetic relevance. The present paper reports a detailed study on the ROCAC between cyclic phosphonites (1) as A-type (ring-opening) monomers and methacrylic and acrylic anhydrides (2) as novel B-type (ring-closing) monomers.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting copolymers (3) have phosphinate-cyclic anhydride structures as ring-opened and ring-closed units, respectively. 2a, R = CH3 1b, m= 3 2b, R = H 3a, m = 2, R = CH3 1 c, m = 4 3b, m = 3, R = CH3 3c, m = 4, R = CH3 3d, m = 2, R = H 3e, m = 3, R = H 3f, m = 4, R = H…”
Section: Introductionmentioning
confidence: 99%